PERLINDUNGAN HUKUM TERHADAP NASABAH DARI KERUGIAN KEGIATAN PERBANKAN YANG DILAKUKAN PEKERJA OUTSOURCING - I Made Aditya Mantara Putra; Ketut Adi Wirawan (VYAVAHARA DUTA, 2022)
In banking practice, in the implementation of itsactivities, there are many problems. This problem often results in losses experienced by bank customers in banking activities. Liability for losses from bank customers is generally replaced by the Bank. Based on the reasoning that the convict committed the unlawful act in the capacity of serving as a relation manager at the bank. Of course, customer losses are the responsibility of the bank, in the perspective of a business entity (corporate). However , the problem will be different when the person who commits an unlawful act is carried out as a worker at a bank but in the status of an outsourced worker . However, an outsourced worker is the responsibility of a bank company (on the one hand) and an outsourcing company (on the other). Legal Protection of Customers in Banking Activities is regulated in Article 46 to 53 of Law Number 10 of 1998 concerning Amendments to Law Number 7 of 1992 on Banking and Article 4 and Article 19 of Law Number 8 of 1999 concerning Consumer Protection. Based on the theory of justice and legal responsibility, compensation as a form of legal responsibility for customer losses in banking activities is not only borne by the bank, but also the personal actors and the outsourcing company.